The effect of company size, leverage, growth and ownership diffusion on aircraft passenger safety information disclosure - Livia Afrina Panenda; Irwansyah (Proceeding International Conference on Accounting and Finance, 2024)
This research aims to provide empirical evidence regarding the disclosure of safety information for airplane passengers, evidence of the influence of company size on the disclosure of safety information for airplane passengers, evidence of the influence of leverage on the disclosure of safety information for airplane passengers, evidence of the influence of growth on the disclosure of safety information for airplane passengers, evidence of the influence of diffusion. ownership of the disclosure of aircraft passenger safety information to airlines in the world regarding the COVID-19 pandemic. This research is descriptive research. The data collection technique uses documentation methods which will later be analyzed using descriptive statistical methods and eviews.